(untitled) (Confluenţe Bibliologice, 2024)
The presence and involvement of priests’ wives in family life and the parish community is a fundamental aspect of the tradition and organization of the Romanian Orthodox Church. They are viewed as vital support for both the priest and the community, fulfilling multiple roles and responsibilities.Priests’ wives undertake a wide range of activities, from maintaining harmony within the family to coordinating various events and activities within the parish. Through their personal example and active participation, they serve as role models for the community and provide essential support for the spiritual mission of the priest and the Church as a whole.